Computer assisted diagnosis of fine needle aspirate of the breast. Issue 2 (February 1990) - Heathfield, H A; Kirkham, N; Ellis, I O; Winstanley, G
Abstract : The development of the National Breast Screening Programme has created a demand for the widespread availability of fine needle aspiration cytology services. To meet this demand there must be a rapid increase in the number of pathologists and laboratories able to offer this service. In turn there is a need for improved training methods. The technique of fine needle aspiration cytology is not inherently complicated. The number of possible conclusions is essentially limited to four: unsatisfactory, benign, suspicious and malignant. A computer based expert system, designed to assist pathologists in the diagnosis of fine needle aspirates of the breast, has been developed. The system prompts pathologists to categorize a number of variables in the aspirate including nuclear and cytoplasmic features, and the degree of cellular cohesion, and uses these data to reason about possible conclusions. The final diagnosis is displayed with a detailed explanation listing the factors supporting it. Initial trials with this system have been encouraging and it is envisaged that this system will be of value both in training and as an aid to routine diagnosis.